Sleep Architecture, Muscle Function, and Daily Life Activities in Patients with Sarcopenia - López-Ramírez, Eduardo; Millán-Rosas, Gabriela; Santana-Miranda, Rafael; Santana-Vargas, Daniel; Poblano, Adrián; Gutiérrez-Escobar, Romel (Sleep Science, 2025)
To examine associations between polysomnography, muscle mass and strength, and daily life activity index (DLAI) in patients with sarcopenia.We measured polysomnography, muscle mass and strength, and DLAI in 16 patients with sarcopenia and 26 controls > 60 years old and then compared variables and correlations in the patients with sarcopenia.We found no differences in polysomnography between patients with sarcopenia and controls. Among patients with sarcopenia, latency to rapid eye-movement (REM) sleep was positively correlated with weight, REM %, and total sleep time was positively correlated with grip strength. Latency of REM sleep was negatively correlated with body mass index, NREM sleep, and apnea index was negatively correlated with grip strength. Daily life activity index correlated positively with grip strength.Patients with sarcopenia showed significant correlations between polysomnography and weight, body mass index, and grip strength, suggesting a complex relationship involving sleep architecture, muscle function, and DLAI that deserves more research.
Keywords: sarcopenia; polysomnography; muscle mass; grip strength; daily life activities index